Implementation Enterprise Resource Planning Sales and Purchase of Goods Using WebERP Fushia Clothing Store Denpasar - Sampe, Irianto Yohanes; Eka Pratama, I Putu Agus; Mandenni, Ni Made Ika Marini (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2023)
The application of integrated information systems in business requires improvements related to system performance. A business can run well if every division in it is integrated with one another. One of the obstacles in this research is that the sales business process is still done manually, data storage on Ms. Excel, and between divisions one with other divisions have not been integrated. The technology proposed as a solution to these problems is Enterprise Resource Planning. This research was conducted by implementing the ERP model using WebERP which is used to assist the entire series of business processes at Fushia Stores. The research conducted focuses on three parts of the process, namely on the Sales, Purchase, and Inventory sections. The implemented implementation has met the needs of Fushia Stores with a system trial result of 71.66% or the equivalent of an agree index scale. The system implemented is able to improve and integrate all data so that data processing becomes more effective and efficient to use. Keywords: Business Process, Enterprise Resource Planning, Fushia Shop, Likert Scala, WebERP.